Christology of the Old Testament - Hegstenberg, Ernst Wilhelm (W. M. Morrison, 1836)
1. General introduction and the Messianic prophecies of Isaiah.- 2. Messianic prophecies of Zechariah and Daniel.- 3. [Messianic prophecies of Hosea, Joel, Amos, Micah, Haggai, Malachi, Jeremiah, Ezekiel]